2020
DOI: 10.3389/fimmu.2020.587669
|View full text |Cite
|
Sign up to set email alerts
|

Low Mannose Binding Lectin, but Not L-Ficolin, Is Associated With Spontaneous Clearance of Hepatitis C Virus After Infection

Abstract: Some individuals can spontaneously clear the hepatitis C virus (HCV) after infection, whereas others develop a chronic infection. The exact mechanism of this phenomenon is unknown. We aimed to evaluate the association of plasma levels of MBL, L-ficolin, and cytokines with outcome of HCV infections in two groups of patients who cleared HCV spontaneously (CHS), and who developed chronic HCV infections (CHC). Altogether, 86 patients and 183 healthy controls were included. Of 86 patients, 36 had CHS and 50 had CHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…A study has already reported that low levels of MBL help in eliminating the hepatitis C virus (Zhang et al 2020 ). In contrast, higher serum MBL levels positively correlate to the mortality risk in ICU patients with A(H1N1) pdm09 infection (Zogheib et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study has already reported that low levels of MBL help in eliminating the hepatitis C virus (Zhang et al 2020 ). In contrast, higher serum MBL levels positively correlate to the mortality risk in ICU patients with A(H1N1) pdm09 infection (Zogheib et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the concentration of MBL is genetically determined, there are some other factors affecting MBL level such as bacterial infection, for example caused by Streptococcus pneumoniae ( 3 ) or viral infection resulting in hepatitis C ( 4 ) or COVID-19 ( 5 ).…”
Section: Introductionmentioning
confidence: 99%